2022
DOI: 10.3389/fpubh.2022.837513
|View full text |Cite
|
Sign up to set email alerts
|

Shedding Light on SARS-CoV-2, COVID-19, COVID-19 Vaccination, and Auditory Symptoms: Causality or Spurious Conjunction?

Abstract: There are reports of associations between SARS-CoV2, COVID-19, COVID-19 vaccines, and auditory symptoms (hearing difficulty, tinnitus). However, most studies have relied on self-report and lack baseline and/or non-COVID control groups. This makes it problematic to differentiate if symptoms are associated with SARS-CoV2, COVID-19, the vaccine, psychosocial factors or recall bias. In this study, we differentiate these by comparing hearing and tinnitus survey data collected pre- and during the pandemic. The surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 30 publications
1
12
1
Order By: Relevance
“…We found that in patients who have contracted COVID-19, tinnitus loudness and THI score increased significantly ( Table 3 ). Our findings agree with Saunders et al, who also observed worsening tinnitus complaints in 23.1% of patients with preexisting tinnitus who contracted COVID-19 ( 12 ). However, in addition to the open question also used by Saunders et al, we used a validated instrument to measure the degree of tinnitus complaints and compared the values to the pre-pandemic ones.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We found that in patients who have contracted COVID-19, tinnitus loudness and THI score increased significantly ( Table 3 ). Our findings agree with Saunders et al, who also observed worsening tinnitus complaints in 23.1% of patients with preexisting tinnitus who contracted COVID-19 ( 12 ). However, in addition to the open question also used by Saunders et al, we used a validated instrument to measure the degree of tinnitus complaints and compared the values to the pre-pandemic ones.…”
Section: Discussionsupporting
confidence: 93%
“…Although the scores indicating tinnitus annoyance, tinnitus effect on life, tinnitus effect on sleep, and HQ scores were higher after COVID-19, the differences before-after were not statistically significant. Additionally, as stated in the current literature, the relationship between COVID-19 and the onset of auditory symptoms or worsening of the preexisting ones might depend on the negative effects of the pandemic process and, therefore, should be established with care ( 12 , 43 ).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…On the other hand, the use of ototoxic medications, such as chloroquine, in some COVID-19 patients may have acted as a confounding factor, making an accurate differentiation between ototoxicity and an actual virus-related SSNHL hard to achieve [ 44 ]. However, the consistency of the hypotheses around the causative link between COVID-19 and audiovestibular symptoms may be affected by possible biases resulting from the symptom reporting methods employed in the published studies, as suggested by Saunders et al [ 45 ]. In fact, the nocebo effect might have led some COVID-19 patients to complain, for the first time during the infection period, about symptoms they had experienced before.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that the subjective participant reports were inconsistent, included possible recall bias, and may have been biased due to a nocebo effect. 15 Thus, the limitations of case, case–control, and subjective studies have raised the need for additional audiological measurements and comparisons among COVID‐19 patients to further investigate the possible effect of the infection on the hearing system.…”
Section: Introductionmentioning
confidence: 99%